CHANGE OF THE HEMOGLOBIN LEVEL DURING THE RESUSCITATION PERIOD IN PATIENTS WITH TRAUMATIC BRAIN INJURY, ACCORDING TO THE CHARACTER OF THE TRAUMA - Magerrambeyli, I.Sh.; Kerimova, T.B.; Mirza, V.S.; Guliev, E.R. (World of Medicine and Biology, 2024)
The purpose of the study was to determine a possible relationship between the nature of the injury and hemoglobin levels in patients admitted to hospital with traumatic brain injury. The study included 299 trauma patients admitted to the Clinical Medical Center within 1–1.5 hours after trauma. In addition to dividing the patients by gender, they were divided into age ranges and the origin of the injury. The patients were analyzed in 4 groups depending on the isolation of the traumatic brain injury or its combination with other injuries. In each group, hemoglobin levels were determined in blood samples 4 times on the 1st, 2nd, 3rd, and 4th days. The average level of this parameter in individuals with traumatic brain injury was 97.4±2.5 g/L (50.0–157.0 g/L). In 32 patients who suffered a mixed form of injury, the average value was 88.8±3.2 g/L (50.0–142.0 g/L). The results show that there were no significant differences between the hemoglobin level in the blood and the nature of craniocerebral injuries. However, it is undoubtedly important to conduct a study of patients with craniocerebral injury in the acute period of pathology.